RELIGIOUS AND COGNITIVE DEVELOPMENT AGES 6–12 - Situ Nuraini Situ Nuraini; Salami Mahmud; Miftahuljannah; Zulfahmi (Jurnal Ikhtibar Nusantara, 2026)
Religious and cognitive development in children aged 6–12 years is a fundamental aspect that influences each other in the process of character building and moral understanding. At this stage, children enter the concrete operational stage according to Piaget's theory, which is characterised by logical thinking, reduced egocentrism, and increased ability to classify and understand cause-and-effect relationships. These developmental characteristics play an important role in how children interpret religious teachings, which are generally still literal and concrete in nature. According to Fowler's theory of religious development, children at this age are in the Mythic–Literal Faith stage, where moral values and religious teachings are understood through stories, symbols, and role models. In addition, moral development according to Kohlberg shows that children begin to adjust their behaviour to social norms and authorities that are considered important. The interaction between cognitive and religious development emphasises the importance of an approach to religious education that is appropriate to the child's stage of development. The use of concrete, narrative, and applicative learning methods is crucial to help children understand religious concepts in a more meaningful way. Thus, understanding the dynamics of this development can support effective religious education strategies oriented towards the formation of long-term moral values.